Parole di pietra. Epigrafia, studio dell’antico e nuove architetture nel Rinascimento meridionale - de Divitiis, Bianca; Lenzo, Fulvio (Opus Incertum, 2022)
This article presents the first results of an ongoing research on inscriptions in southern Italy in the late medieval and early modern periods and analyses three different ways in which inscriptions were used to make a façade ‘speak’. In first instance, it analyses two significant examples of ‘written’ buildings, where epigraphic texts played a central role in the overall ‘all’antica’ design of the façade; it subsequently considers those cases in which a monumental and long inscription traversed the entire facade; and finally it focuses on the inscriptions connected to city gates and palace portals, as well as on those cases in which it is the door itself to speak in first person. The cases presented allow us to recognise the ‘speaking façades’ created in the Kingdom of Naples as a self-aware phenomenon which relied on a consolidated tradition regarding the study of local antiquities and on a sense of continuity with both the classical and medieval past.